Gastro-Oesophageal Reflux in Noncystic Fibrosis Bronchiectasis - Lee, Annemarie L.; Button, Brenda M.; Denehy, Linda; Wilson, John W. (Pulmonary Medicine, 2011)
The clinical presentation of noncystic fibrosis bronchiectasis may be complicated by concomitant conditions, including gastro-oesophageal reflux (GOR). Increased acidic GOR is principally caused by gastro-oesophageal junction incompetence and may arise from lower oesophageal sphincter hypotension, including transient relaxations, hiatus hernia, and oesophageal dysmotility. Specific pathophysiological features which are characteristic of respiratory diseases including coughing may further increase the risk of GOR in bronchiectasis. Reflux may impact on lung disease severity by two mechanisms, reflex bronchoconstriction and pulmonary microaspiration. Symptomatic and clinically silent reflux has been detected in bronchiectasis, with the prevalence of 26 to 75%. The cause and effect relationship has not been established, but preliminary reports suggest that GOR may influence the severity of bronchiectasis. Further studies examining the implications of GOR in this condition, including its effect across the disease spectrum using a combination of diagnostic tools, will clarify the clinical significance of this comorbidity.